Microwave-Assisted Oxidation of Cyclohexanecarboxamide by Di-Tertiary-Butyl Chromate in Organic Media: Synthesis and Characterization of Products (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Microwave irradiation has emerged as a transformative technique in organic synthesis, enabling rapid and energy-efficient chemical transformations. This study investigates the oxidative potential of di-tert-butyl chromate (TBC) in the oxidation of cyclohexanecarboxamide, aiming to develop a faster, sustainable alternative to traditional thermal reflux methods. The oxidation was explored across three distinct organic solvent systems: tetrahydrofuran (THF), 1,4-dioxane, and dichloromethane (DCM). Reaction mixtures were prepared by combining substrate solutions with TBC at standardized stoichiometric ratios. Synthesis was conducted using microwave irradiation for precisely calibrated periods (44–110 s). The resulting coordination complexes were characterized through elemental analysis, Fourier-transform infrared (FTIR) spectroscopy, and thermal analyses, including differential thermal analysis (DTA) and thermogravimetric analysis (TGA). The microwave-assisted approach demonstrated significant kinetic enhancement, reducing reaction times from several hours to under two minutes. Solvent-dielectric synergy was observed, with THF providing the highest efficiency and yield. Characterization confirmed the formation of stable binuclear Cr2O3 cores stabilized by a homologous series of dicarboxylate ligands. Mass loss patterns from TGA/DTA further validated the empirical formulations and structural stability of the synthesized complexes. Our findings demonstrate that this microwave-assisted methodology aligns with the principles of green chemistry by minimizing reaction time and energy expenditure. This study provides an efficient and sustainable synthetic route for the oxidation of cyclohexanecarboxamide, offering a versatile template for the development of higher-order chromium (III) coordination frameworks.